F is for Freudian: 4 Erotic Short Stories - Södergran, Alexandra (Saga Egmont, 2023)
'F is for Freudian: 4 Erotic Short Stories' is a collection of erotica that explores the taboo sexual encounters that would not only prove Freud right, but make him hot under the collar too.